PENDIDIKAN ANAK SEJAK PRANIKAH (Studi Tinjauan Hadis) - Fu’ad Arif Noor (STPI Bina Insan Mulia Yogyakarta, 2021)
This research reveals its importance of holding tight selection in choosing a life partner from the family environment and healthy and good. In choosing a wife, Islam teaches Muslim men to pay attention to two things: first, lineage candidate's wife, and secondly, the environment in which he lived and the extent of this environmental impact on personality. A true benchmark in choosing a wife is a woman's level of faith and loyalty to his religion. As mothers and fathers play a very important role in child development, physical, and mental and mental. Therefore, in choosing a husband, Islam also teaches to pay attention to the descent and the environment in which he lived. The prospective husband should also have properties that commendable because it will become role models of their children and bring down all the qualities and character to them. In addition, the wife will also be affected by some of its properties through daily interaction with her. Therefore, the Prophet Muhammad. encourages women to choose husbands were worth it. Criteria for choosing a mate, both for men and women are